Association between mental health and attitudes towards confinement during the COVID-19 pandemic in hospitals in Lima and Callao - Campos-De La Cruz, Iris (2021)
Objective: Identify the association between depression, anxiety and stress with attitudes towards confinement during the COVID-19 pandemic in health staff from the Daniel Alcides Carrion National Hospital and Central Military Hospital by using the DASS-21 scale. Materials and methods: Cross-sectional, observational and analytical study, health staff participated who worked in COVID areas during the Covid-19 pandemic. The Dass-21 scale was used to measure the existence of emotional states of depression, anxiety and stress, and the scale of attitudes adapted to confinement for Covid-19. Results: 124 participants were included, 54% female (n=67), with a median age of 34.5 years [Ri]= 16.5, who reported a median year of experience of 6 (Ri = 17). The median Dass-21 score for anxiety was 2 (Ri = 5), the median Dass-21 score for depression was 1 (Ri = 4.5), and the median Dass-21 scale score for stress was 4 (Ri = 5). The bivariate analysis between the values of the Dass-21 Scale domains and the other covariates identified that the level of education had a highly significant relationship with the depression subscale, anxiety and stress. Conclusion: An association was found between the affective parameters of the scale on attitudes towards confinement and the three subscales of DASS-21.